Analysis of Sanitary Hygiene Conditions in Ampera Mintuo, Perhentian Marpoyan Village, Marpoyan Damai District, Pekanbaru City in 2022: Analisis Kondisi Hygiene Sanitasi Ampera Mintuo Kelurahan Perhentian Marpoyan Kecamatan Marpoyan Damai Kota Pekanbaru Tahun 2022 - Wan Sonia Fahira; Riri Maharani; Christine Vita G.P; Hetty Ismainar; Nurvi Susanti (Badnur Medisa Group, 2022)
Hygiene is an effort to prevent a disease in individuals or humans and the environment in which the person is located. The restaurant is one of the places visited by the general public, this requires special attention in the field of sanitation. The purpose of this study was to determine the analysis of hygiene and sanitation conditions of Ampera Mintuo in Perhentian Marpoyan Subdistrict, Marpoyan Peace District, Pekanbaru City in 2022. The type of research was qualitative with a qualitative descriptive. The informants in this study were 9 people, namely, the sanitarian section of the puskesmas, 2 people, restaurant owners, 3 kitchen employees, 2 handlers, 1 Ampera visitors. This research has been carried out in July 2022. The results of this study indicate that the handlers do not use masks, do not use gloves and do not wash their hands when making food for buyers, Equipment is not washed with running water, utensils are washed with water that is stored in a basin and the water is already oily due to the previous dishwashing, the equipment storage area is open, the water container is not closed, it is hoped that handlers will use masks because of the pandemic using masks can prevent the spread of covid-19, equipment must be washed with running water, The equipment storage area should be placed in a special equipment cabinet to avoid vectors from entering the equipment.